PEMANFAATAN VARIASI TEKNOLOGI GUNA MENINGKATKAN MOTIVASI BELAJAR DALAM PEMBELAJARAN DARING BAHASA INDONESIA (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
Learning with the current pandemic condition is a new condition for many educators. The limitations of online learning are of course a problem. As a result, there is less motivation to learn. Increased motivation to learn becomes a bigger portion of learning. This paper is a literature review that aims to describe and at the same time explain the importance of using various technologies in Indonesian language learning in order to increase students' learning motivation. The use of various technologies such as padlet, quizizz, mentimeter, and so on can be a solution in increasing student motivation.